The Macroeconomic Effects of the Taylor Rule Deviations in Central and Eastern European Countries - Shevchuk, Viktor (Efekty makroekonomiczne odchyleń od reguły Taylora w gospodarkach Europy Środkowej i Wschodniej, 2023)
A standard Taylor rule was estimated for several Central and Eastern European (CEE) countries (Czechia, Hungary, Poland, Romania) based on quarterly data over the 2002-2021 period. The SVAR model indicates, for all CEE countries, that the level of central bank policy rate below the Taylor rule implied rate is caused by both output gap and inflation, with the Taylor rule deviations having heterogeneous effects on other endogenous variables. Among other results, the depreciation of the exchange rate is contractionary and inflationary, the output gap is inflationary (except for Romania), while inflationary effects on output are different across the CEE countries.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2023; vol. 67, nr 4, s. 132-142
Keywords: Taylor rule; output; inflation; exchange rate; SVAR; reguła Taylora; dochód; inflacja; kurs walutowy